Good fiction guide - Jane Rogers; consultant editor; Hermione Lee; assistant editors; Mike Harris; Douglas Houston; assistant editor on the paperback edition; Daniel Hahn (Oxford University Press, 2005)
Let this guide help you choose a book that you really want to read from over 4,200 titles. Featuring both subject essays and over 1,100 alphabetically arranged entries on writers ranging from Maeve Binchy to Emile Zola, this is an invaluable guide for anyone trying to find their way around the mass of fiction in bookshops. 34 well-recognised authors and critics introduce literary genres. John Sutherland on Classics, Val McDermid on Thrillers, and Michele Roberts on France are just a few of the experts who recommend their personal top twelve favourite reads within their subject areas. Covering a wide range of fiction; classical and contemporary, literary and popular, British and foreign; each entry also suggests other authors who deal with similar subject matters or write in the same genre. The entries aim to provide a flavour of each writer's work and give recommendations of which of their books to read. A snapshot of English literature at the beginning of the twenty-first century